Genetical structure of cawpea populations and its implication on the genetic improvement through selection - Aquino, Solange Felicidade de; Nunes, Raimundo de Pontes (Pesquisa Agropecuaria Brasileira, 2014)
Two hypothesis about the genetical structure of varieties and populations of cowpea, Vigna unguiculata (L.) Walp, were tested under the assumption of two different mathematical models. Genetic variability of two cultivars were studied in respect to the terms of the assumed models, and components of genetic variance were estimated. The number of generations for which genetic advance is achieved under three different selection procedures was determined for several yield components.